Effect of microemulsion on low-rank coal flotation by mixing DTAB and diesel oil. (15th January 2020) - Zhang, Rui; Xia, Yangchao; Guo, Fangyu; Sun, Wei; Cheng, Hongzhi; Xing, Yaowen; Gui, Xiahui
Graphical abstract: Highlights: Dosage of diesel oil reduced effectively using micro-emulsion. Effect of different ratio of micro-emulsion on flotation effect was studied. Micro-emulsion improves the dispersion of diesel oil on the coal surface. There is synergistic effect between diesel oil and DTAB. Abstract: It is difficult to recover low-rank coal using traditional oily collectors because a large number of oxygen-containing functional groups and pores exist on its surface. In this study, a microemulsion was prepared by mixing dodecyl trimethylammonium bromide (DTAB) and diesel oil; its effect on low-rank coal flotation was studied via water contact angle and wrap angle measurements. The results show that the clean coal could not be effectively recovered using a single reagent of DTAB or diesel oil. However, the microemulsion can improve the clean coal recovery with a small amount of diesel oil. The recovery of clean coal was greatest when the mass ratio of DTAB and diesel was 1:2. The addition of DTAB could act as a dispersant in the oily collector, and thus increased the contact area between coal and reagent. More importantly, DTAB and diesel oil could be adsorbed on the low-rank coal surface because of their synergistic effect. On the one hand, DTAB can improve the dispersion of diesel oil. On the other hand, the combination of diesel and DTAB promoted the spread of diesel on the particle surface. The microemulsion could improve the hydrophobicity and floatability of coal particles and enhance the stability of particle-bubble adhesion. The relationship between wrap angle and time could be well fitted by the first-order kinetic equation and the results show that the attachment rate gradually increased and reached its maximum when the mass ratio of DTAB and diesel was 1:2.